EVALUATION OF RESULTS IN THE MEANINGFUL LEARNING OF MATHEMATICS IN HIGH SCHOOL - Gomez Hernandez, Julia Angela; Ferbol Ramirez, Cristina Elizabeth; Díaz Alvarado, Mauricio Andrés (My University, 2024)
The current article aims to analyze the evaluation of results in the meaningful learning of mathematics in basic education students in a private high school located in the commune of Punta Arenas-region of Magallanes, it was framed in the quantitative approach, with a basic typology and the design in a non-experimental state, the population consisting of 68 students from the aforementioned high school. To obtain the information, a questionnaire with a Likert scale was used, validated under the judgment of experts and the reliability of Cronbach's Alpha. The main findings in the communication indicator reveal a significant negative perception regarding the effectiveness of the strategies used to promote student dialogue. Furthermore, the indicator ability to solve problems shows an insufficiency of the pedagogical practices used, which would not be able to strengthen the skills necessary for students to address and solve mathematical problems effectively.
Avaliação de resultados na aprendizagem significativa de matemática em estudantes do Ensino Médio
EVALUACIÓN DE RESULTADOS EN EL APRENDIZAJE SIGNIFICATIVO DE LA MATEMÁTICA EN ESTUDIANTES DE ENSEÑANZA MEDIA
Keywords: assessment; results; learning; significant; mathematics